The role of long non-coding RNA in abdominal aortic aneurysm - Xu, Yi; Yang, Shuofei; Xue, Guanhua (Frontiers in Genetics, 2023)
The abdominal aortic aneurysm (AAA) is characterized by a gradual segmental enlargement of the abdominal aorta and a significant death rate. Apoptosis of smooth muscle cells, the creation of reactive oxygen species, and inflammation are a few probable pathways for the formation and development of AAA that are suggested by the characteristics of AAA. Long non-coding RNA (lncRNAs) are becoming a new, essential regulator of gene expression. In order to employ these lncRNA as clinical biomarkers and new treatment targets for AAAs, researchers and physicians are focusing on them. Studies on lncRNA are just starting to come out, which indicates that they may have a significant and as yet unidentified function in vascular physiology and disease. This review discusses the function of lncRNA and their target genes in AAA with the goal of improving our knowledge of AAA initiation and progression, which is essential for the creation of possible AAA therapeutics.